Why Is The Rate of Profit Still Falling? - Thomas R. Michl (Levy Economics Institute of Bard College, 1988)
This paper elaborates a fixed-coefficient, capital, labor, non-raw material intermediates, raw materials production model; estimates the wage share-profit rate frontier associated with it for U.S. manufacturing from 1949 to 1986; and suggests the following explanation of declining profitability. From 1949 to 1970, a rising wage share drove the manufacturing industries up along the wage-profit frontier. Declines in relative raw material prices shifted the frontier out in this period. From 1970 to 1986, raw material prices shocks shifted the frontier in, but as raw material prices declined in the 1980s, the failure of either the wage share or the rate of profit to recover to their previous levels suggests that a secular decline in the output-capital ratio has rotated the frontier inwards. This finding has significance for the tneory of technical change.
Keywords: 330